Segmentation and regional analysis: labor typologies and geographic inequality in Antofagasta and La Araucanía, Chile - Blanco, Osvaldo; Julián-Véjar, Dasten; Osorio-Rauld, Alejandro (Frontiers in Sociology, 2025)
This article examines the geographic variability of labour markets in the Chilean regions of Antofagasta and La Araucanía, emphasizing their structural similarities and differences. An inter- and intraregional perspective is applied to identify common and specific elements in both territories, drawing on multivariate sociodemographic, contractual, and occupational data. Through factorization and cluster analysis, typological systems of labour segmentation are constructed for each region, located at opposite ends of the country. The results reveal the heterogeneity of regional labour matrices, encompassing both regular and protected employment as well as unregulated, temporary, informal, and precarious arrangements. The study also considers the role of urban and rural contexts in shaping productive activities and labour conditions. While extractive industries represent a shared feature of Chile’s productive matrix, the findings show unequal segmentation systems across regions. These differences highlight persistent gender inequalities in access to decent and protected work, along with differentiated patterns of labour insertion for Indigenous peoples and migrants across urban and rural areas. The analysis contributes to understanding regional labour dynamics and underscores the need for territorially differentiated policies that acknowledge the structural diversity of employment conditions in northern and southern Chile.